Subjetividade e intencionalidade: Searle crítico de Dennett - Uzai Júnior, Paulo [UNESP]; Coelho, Jonas Gonçalves [UNESP] (My University, 2013)
We considered John Searle's response to criticisms of Daniel Dennett in relation to the subjective aspect of human consciousness, which involve difficulties that the approach of Searle brings to objective scientific research. Because the replica of Searle consist the defense of the possibility of objective knowledge of subjectivity, we show how the philosopher's response involves the clarification of some points of his theory of consciousness, articulating the intentionality with human subjectivity. For both, we present the main points of his theory of intentionality, looking for understand his close relationship with subjectivity

Consideramos a resposta de John Searle às criticas de Daniel Dennett em relação ao caráter subjetivo da consciência humana, as quais envolvem as dificuldades que a abordagem searleana traz a uma investigação científica objetiva. Como a réplica de Searle consiste na defesa da possibilidade de um conhecimento objetivo da subjetividade, mostramos como a resposta do filósofo envolve o esclarecimento de alguns pontos de sua teoria da consciência, articulando a intencionalidade com a subjetividade humana. Para tanto, apresentamos os principais pontos de sua teoria da intencionalidade, procurando entender a sua estreita relação com a subjetividade.
Subjectivity and intentionality: Searle critic of Dennett
Keywords: John Searle; Daniel Dennett; Consciousness; Intentionality; John Searle; Daniel Dennett; Consciência; Intencionalidade